2019
DOI: 10.31557/apjcp.2019.20.6.1757
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Family-Centered Empowerment Model (FCEM) on the Care Burden of the Parents of Children Diagnosed with Cancer

Abstract: Parents not only constantly reconstruct their roles, functions, interactive and communicative patterns, inside and outside the family, but are also in charge of many caring responsibilities as a result of being the member of the treatment team (Crespo et al., 2016). Clearly, parents not only should tolerate emotional and mental pressure, but also accomplish their medical tasks, parental supervision and all their roles and responsibilities (McGrath, 2002; Grinyer, 2006; Da Silva et al., 2010). Parents of childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 34 publications
1
47
0
Order By: Relevance
“…Another study on the effect of education of mothers of children with cancer undergoing chemotherapy on prevention of the gastrointestinal side effects of chemotherapy showed that educational intervention had a signi cant impact on reducing the effects of chemotherapy [6,32]. An investigation on the effect of educational intervention on the home care behavior of parents having children with cancer undergoing chemotherapy, indicated that the intervention was effective in reducing the effects of chemotherapy [33]. In the present study, the parents received educations about caring behaviors on how to reduce the side effects of chemotherapy at home.…”
Section: Discussionmentioning
confidence: 99%
“…Another study on the effect of education of mothers of children with cancer undergoing chemotherapy on prevention of the gastrointestinal side effects of chemotherapy showed that educational intervention had a signi cant impact on reducing the effects of chemotherapy [6,32]. An investigation on the effect of educational intervention on the home care behavior of parents having children with cancer undergoing chemotherapy, indicated that the intervention was effective in reducing the effects of chemotherapy [33]. In the present study, the parents received educations about caring behaviors on how to reduce the side effects of chemotherapy at home.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are no studies examining the effect of the FCEM and CCM methods and comparing them to standard pulmonary rehabilitation on ARDS survivors. However, few studies have been performed on the effects of these methods on patients with other chronic illness [15][16][17][18][19] . The results of these studies about the use of a FCEM on caregivers and family members of patients with chronic illness, have been shown some improvement in the quality of life and mental health, which was consist with our ndings and reported the implementation of a FCEM intervention can reduce the burden of disease, and improve the mental and physical health of patients [27][28][29] .…”
Section: Discussionmentioning
confidence: 99%
“…The FCEM was developed to improve the care and outcomes of patients with chronic diseases and has previously been evaluated and validated in several chronic disease states 14 . Family engagement in the rehabilitation process may potentially have bene cial effects including improvements in mental and physical function, and reduced burden of disease 18,19 . The primary aim of the model is to empower the patient/family unit to promote health quality.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of this study, the term health care professionals describes health care personnel, including doctors, nurses, and all other formal caregivers, whereas informal cancer caregivers, cancer caregivers, and caregivers are used interchangeably, referring to informal cancer caregivers such as family and friends, who often regularly provide a wide range of assistance to a patient with cancer. Although, overall, a variety of interventions hold promise to alleviate caregiver burden, ranging from print materials and face-to-face consultations to telephone-based assistance [11][12][13][14][15][16][17][18][19][20], technology-based interventions are considered the most practical and promising solution available to caregivers.…”
Section: Introductionmentioning
confidence: 99%